SIAGA SEJAK DINI: SIMULASI MITIGASI UPAYA MENINGKATKAN KESADARAN DAN KESIAPSIAGAAN BENCANA SISWA SEKOLAH DASAR - Kalengkongan, Aurelia Naftali; Bernike Burnama; Mariani Angeline; Saula Rahmadianti Krisma Pertiwi; Novario Jaya Perdana (Jurnal Serina Abdimas, 2025)
An earthquake measuring 5.6 magnitude shook the Cianjur region, including the Ciherang village, on November 21, 2022. Cianjur Regency is classified as an earthquake-prone area in West Java Province, as recorded by the National Disaster Management Agency (BNPB), which noted that the region experienced more than 70 earthquake events in the past three years (BNPB, 2023). The earthquake caused significant damage and highlighted the lack of community preparedness, especially among elementary school children, in facing earthquake disasters. Based on this incident, the Thematic Community Service Program (KKNT) at SDN 01 Ciherang aims to raise awareness and earthquake preparedness among the students of SDN 01 Ciherang through education and earthquake mitigation simulations. The main problem faced by students is the lack of understanding and awareness regarding the appropriate actions to take during an earthquake. The proposed solution is education through a participatory approach that includes counseling and evacuation simulations. This implementation focuses on the socialization of natural disaster material related to earthquakes and the simulation of earthquake mitigation using the Drop, cover, and hold-on method, involving students from grades one to five. The results of the socialization and mitigation simulation activities show an increase in understanding regarding awareness and preparedness during an earthquake, as well as a quicker and more directed response during the simulation. This program proves that early education on mitigation is important in helping students train their awareness and preparedness for earthquakes in both school and surrounding environments. Gempa bumi berkekuatan 5,6 magnitudo mengguncang wilayah cianjur, termasuk desa ciherang, pada tanggal 21 november 2022. Kabupaten cianjur termasuk wilayah rawan gempa bumi di provinsi jawa barat, sebagaimana tercatat oleh Badan Nasional Penanggulangan Bencana, yang mencatat bahwa wilayah cianjur mengalami lebih dari 70 kejadian gempa dalam tiga tahun terakhir (BNPB, 2023). Gempa bumi yang terjadi menimbulkan kerusakan yang signifikan dan menyoroti minimnya kesiapsiagaan masyarakat, khususnya anak-anak sekolah dasar, dalam menghadapi bencana gempa bumi. Berdasarkan kejadian tersebut, program Kuliah Kerja Nyata Tematik (KKNT) Di SDN 01 Ciherang bertujuan untuk meningkatkan kesadaran dan kesiapsiagaan gempa bumi untuk para siswa-siswi SDN 01 Ciherang melalui sosialisasi dan simulasi mitigasi gempa bumi. Permasalahan utama yang dihadapi siswa adalah kurangnya pemahaman dan kesadaran siswa mengenai tindakan yang tepat saat terjadinya gempa. Solusi yang ditawarkan adalah edukasi melalui pendekatan partisipatif yang mencakup penyuluhan dan simulasi evakuasi. Pelaksanaan ini difokuskan pada sosialisasi materi bencana alam gempa bumi serta simulasi mitigasi gempa bumi menggunakan metode Drop, cover, dan hold-on yang melibatkan siswa kelas satu sampai 5. Hasil dari kegiatan sosialisasi dan simulasi mitigasi ini menunjukan adanya peningkatan pemahaman mengenai kesadaran dan kesiapsiagaan saat gempa, serta respon yang lebih cepat dan terarah saat simulasi dilaksanakan. Program ini membuktikan bahwa edukasi mitigasi sejak dini penting dalam membantu siswa untuk melatih kesadaran dan kesiapsiagaan terhadap gempa bumi di lingkungan sekolah maupun lingkungan sekitar.